Energy Literacy and Energy-related Financial Literacy in Iran: Case of Northwestern Academic Community - Davoud Hamidi Razi; Reza Ranjpour; Mohammad Ali Motafakker Azad (Environmental Energy and Economic Research)
Empowering citizens is the most effective way in order to make effective decisions to speed up energy conservation in residential sector. The aim of this study is to investigate the impact of economic and financial literacy on energy literacy and energy awareness in the north west of Iran. The study population consisted of employees and professors of universities in the three provinces of East Azerbaijan, West Azerbaijan and Ardabil that were completed and analyzed 500 questionnaires after sampling. According to the results of Logit model, economic and financial literacy had a significant and positive effect on energy literacy index (selection of heating systems A and B) and energy awareness (energy bills or costs awareness) and the result was confirmed in all the estimation models for three carriers. As the area of the house’s infrastructure area increases, energy literacy increases. Education and age have a negative and positive effect on energy awareness, respectively. The results suggest that investing in promoting energy-related economic and financial literacy for citizens to stimulate energy savings.